Inhibition of astroglial NF-kappaB enhances oligodendrogenesis following spinal cord injury - Bracchi-Ricard, Valerie (BioMed Central, 2013)
BACKGROUND: Astrocytes are taking the center stage in neurotrauma and neurological diseases as they appear to play a dominant role in the inflammatory processes associated with these conditions. Previously, we reported that inhibiting NF-κB activation in astrocytes, using a transgenic mouse model (GFAP-IκBα-dn mice), results in improved functional recovery, increased white matter preservation and axonal sparing following spinal cord injury (SCI). In the present study, we sought to determine whether this improvement, due to inhibiting NF-κB activation in astrocytes, could be the result of enhanced oligodendrogenesis in our transgenic mice. METHODS: To assess oligodendrogenesis in GFAP-IκBα-dn compared to wild-type (WT) littermate mice following SCI, we used bromodeoxyuridine labeling along with cell-specific immuno-histochemistry, confocal microscopy and quantitative cell counts. To further gain insight into the underlying molecular mechanisms leading to increased white matter, we performed a microarray analysis in naïve and 3 days, 3 and 6 weeks following SCI in GFAP-IκBα-dn and WT littermate mice. RESULTS: Inhibition of astroglial NF-κB in GFAP-IκBα-dn mice resulted in enhanced oligodendrogenesis 6 weeks following SCI and was associated with increased levels of myelin proteolipid protein compared to spinal cord injured WT mice. The microarray data showed a large number of differentially expressed genes involved in inflammatory and immune response between WT and transgenic mice. We did not find any difference in the number of microglia/leukocytes infiltrating the spinal cord but did find differences in their level of expression of toll-like receptor 4. We also found increased expression of the chemokine receptor CXCR4 on oligodendrocyte progenitor cells and mature oligodendrocytes in the transgenic mice. Finally TNF receptor 2 levels were significantly higher in the transgenic mice compared to WT following injury. CONCLUSIONS: These studies suggest that one of the beneficial roles of blocking NF-κB in astrocytes is to promote oligodendrogenesis through alteration of the inflammatory environment.